The situation of horticultural family farms in Hajdu-Bihar County - D. Nagyné-Demeter (International Journal of Horticultural Science, 2010)
The main aim of this research work is to study horticultural farms in Hajdú-Bihar County, that mobilize labour and capital for the sake of agricultural production, namely family farms. During this study work we tried to chart the main characters, the conditions of functioning, their profitability and its use possibilities, their external contacts and the resource of information of these farms, beside this to investigate the relationships between these parameters. Parallel to this we tried to compensate the relatively high deficiency of information by empirical research work. This deficiency is the characterization of farmers and the inducement of farming and its conditions both on the level of county and state. By our empirical research work we have made a comprehensive position paper that shows the conditions of farms and farmer populations, as well. Two hundred questionnaires were evaluated. The percentages of horticultural farms were 25% from all questionnaires. Above all this paper is looking for the answer to the following questions: How and by which sources do farmers develop and extent their farms? How do farmers see their own future, what kind of aims do they have?Who will stop and who will go on producing? The collected information on the whole may help to make much more flexible legislatives and administrative regulations, although the survey covered only one county.